Sustainable business eventsand usage of information technology / Norol Hamiza Zamzuri … [et al.] - Zamzuri, Norol Hamiza; Awang, Khairil Wahidin; Abdul Aziz, Yuhanis; Samdin, Zaiton (Universiti Teknologi MARA Cawangan Selangor, 2015)
Sustainable business events demand the commitment of event practitioners. Information technology is used in mitigating the process of sustainable business events. Thus, the aim of this study is to explore the role of information technology in the process of organizing a business event as it was found that there is lack of knowledge on how to organize a sustainable business event in the Malaysian context. It was found that using information technology assists the process of organizing an event through the use of several technological devices and reducing the use of paper. For this reason, inductive methods with 14 informants were studied involving company directors, event managers, venue providers, event delegates and event suppliers. It was found that the role of information technology is important to mitigate the process of organizing a business event. Triangulation was used to ensure the reliability of the findings and members’ check and interview protocols were used for validation purposes. The constant comparison on method of analysis was used to analyze information that result from semi-structured interview. Keywords: Sustainable business event, process, inductive, constant comparison and information technology